Análisis de la estructura temporal de la Archivística Eclesiástica - Vivas Moreno, Agustín; Pérez Ortiz, Mª Guadalupe (Revista General de Información y Documentación, 2009)
The main objective of this article is to build up baselines for a History of Ecclesiasctic Archival. For this purpose, we will establish periods of certain historical homogeneity, moreover We will bear in mind the stages of the general Archival history and we will speak about four big moments: Archival science as an inductive and functional instrument, Archival science as patrimonial and legal-administrative field, Archival science as a historiographic development, and Archival science in knowledge society. In consequence, we infer as a main result that understanding spaces are basic for comprehension of archival science cultural history, a ground-breaking concept.